Robust fixed-time trajectory tracking control of marine surface vessel with feedforward disturbance compensation - Yao, Qijia (International journal of systems science, 2022)
This paper proposes a novel robust fixed-time control approach for the trajectory tracking control of a fully actuated marine surface vessel (MSV) subject to system uncertainties and external disturbances. First, a nominal fixed-time controller is originally designed based on the bi-limit homogeneous method. The nominal fixed-time controller can guarantee the position and velocity tracking errors converge to zero in fixed time in the absence of lumped disturbance. Then, a new type of fixed-time disturbance observer is introduced to estimate the lumped disturbance in fixed time. Finally, a robust fixed-time controller is developed by integrating the nominal fixed-time controller with the fixed-time disturbance observer. The robust fixed-time controller can guarantee the position and velocity tracking errors converge to zero in fixed time even in the presence of lumped disturbance. Benefiting from the feedforward disturbance compensation, the robust fixed-time controller has the strong robustness and excellent disturbance attenuation capability. Numerical simulations and comparisons demonstrate the effectiveness and advantages of the proposed control approach.